Spin-1 Models in the Ultrastrong-Coupling Regime of Circuit Qed - Retamal-Abarzua, J; Romero-Huenchunir, G; Albarran-Arriagada, F (American Physical Society, 2018)
We propose a superconducting circuit platform for simulating spin-1 models. To this purpose we consider a chain of N ultrastrongly coupled qubit-resonator systems interacting through a grounded superconducting quantum interference device (SQUID). The anharmonic spectrum of the qubit-resonator system and the selection rules imposed by the global parity symmetry allow us to activate well controlled two-body quantum gates via ac pulses applied to the SQUID. We show that our proposal has the same simulation time for any number of spin-1 interacting particles. This scheme may be implemented within the state-of-the-art circuit QED in the ultrastrong coupling regime. © 2018 American Physical Society.